Determination of the Electronic Energy Levels of Colloidal Nanocrystals using Field-Effect Transistors and Ab-Initio Calculations - Bisri, Satria Zulkarnaen; Degoli, Elena; Spallanzani, Nicola; Krishnan, Gopi; Kooi, Bart Jan; Ghica, Corneliu; Yarema, Maksym; Heiß, Wolfgang; Pulci, Olivia; Ossicini, Stefano; Loi, Maria Antonietta (Advanced Materials, 2014)
Colloidal nanocrystals electronic energy levels are determined by strong size-dependent quantum confinement. Understanding the configuration of the energy levels of nanocrystal superlattices is vital in order to use them in heterostructures with other materials. A powerful method is reported to determine the energy levels of PbS nanocrystal assemblies by combining the utilization of electric-double-layer-gated transistors and advanced ab-initio theory.
Keywords: ab-initio; colloidal nanocrystals; field-effect transistors; ionic liquid; quantum dots